Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Premier Qualitas Indonesia Cabang Premier Pavilion Pegadungan Jakarta - Anisah; Furi Indriyani; Rohani Lestari Napitupulu (PT. Pustaka Cendekia Publisher, 2024)
The aspect of human resources is the most critical concern for an organization because the success or failure of an organization depends on the management of human resources. This study aims to determine the influence of Leadership and Work Environment on Employee Performance at PT. Premier Qualitas Indonesia Premier Pavilion Pegadungan Jakarta Branch. This type of research uses quantitative descriptive research using numerical illustrative methods by describing processed numbers that will be obtained from IBM Spss Version 26. The sample in this study is part of the total population; for sampling in this study, the researcher used a saturated sampling technique of as many as 30 respondents. This research instrument is by distributing questionnaires. The results of this study show that the regression equation Y 14.867 + 0.109 X1 + 0.579 X2 partially does not affect employee performance. In contrast, the work environment partially affects employee performance, and simultaneously, leadership and work environment have a positive and significant effect on employee performance, with an R square value of 33.9 or 33.9%. In contrast, the remaining 66.1% is influenced by other factors that have not been studied.